IMPROVED EXPONENTIAL APPROACH METHOD DAN ZERO SUFFIX METHOD DALAM MENENTUKAN SOLUSI OPTIMAL PADA MASALAH TRANSPORTASI - ISTIQOMAH, ISTIQOMAH; TASTRAWATI, NI KETUT TARI; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 11 No 1 (2022), 2022)
The problem of transportation is a problem of distributing goods from several sources to several destinations with the aim of minimizing shipping costs. Distribution activities in a company sometimes experience problems in transportation problems so that a model is needed to determine the optimal distribution using the transportation model. This study aims to determine the route of distribution of beras putri sejati 25 kg  in UD Sinar Jaya Abadi so that optimal expenses can be obtained using improved exponential approach and zero suffix method. Based on the calculation results, both methods produce the same three distribution path. The first distribution channel is from Agen Monang Maning to Toko Mekar Sari and Subur Jaya. The second distribution line from the Agen Gatsu Barat to UD Mas Ayana and Toko Dharma. The third line from agen Gianyar to UD Sinar Wangi, Toko Sari Artha, UD Amertha, and Toko Ayu Mega with optimal distribution costs of Rp 1.575.815.00. The difference or efficiency of the total costs incurred in the distribution before and after optimization by UD Sinar Jaya Abadi Rp 499,190.00 or 24%.